Physicochemical and microbiological properties of fermented milk using lactic acid bacteria isolated from dangke (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Syah SP, Mukhlisah AN, Ningtiyas WD, Irfan M, Ananda N, Amalia A, Tasmin. 2024. Physicochemical and microbiological properties of fermented milk using lactic acid bacteria isolated from dangke. Biodiversitas 25: 3876-3883. This study aimed to investigate the effect of milk and starter culture type (commercial and lactic acid bacteria (LAB) isolated from dangke). Two strains of LAB (Lactobacillus fermentum A323L and B111K) and commercial culture were tested for physicochemical and microbiological properties in milk fermentation. The results showed that the type of culture had a significant effect (p